Phase 2 trial (NCI-COTC030) of adjuvant inhaled recombinant human IL-15 combined with amputation and adjuvant chemotherapy in dogs with appendicular osteosarcoma - Rebhun, Robert B.; Cruz, Sylvia M.; York, Daniel; Mazcko, Christina N.; Razmara, Aryana M.; Patkar, Sushant; Judge, Sean J.; Sholevar, Cyrus J.; Shah, Ravi K.; Zamora, Anthony E.; Al-Nadaf, Sami; Vail, David M.; et al. (Frontiers in Immunology, 2025)
BackgroundWe have previously shown inhaled IL-15 is associated with anti-tumor responses in dogs with metastatic osteosarcoma (OSA) and melanoma. We evaluated inhaled IL-15 combined with amputation and chemotherapy for localized canine OSA eligible for treatment with curative intent.MethodsIn a multicenter COTC phase-II-trial for dogs with limb OSA, we hypothesized 2 weeks of inhaled rhIL-15 after amputation and prior to chemotherapy would reduce the risk of metastatic failure at the completion of chemotherapy from a historical rate of 40% to 20%. Using a 2-sided alpha of 0.05, we planned an accrual of 40 dogs to test this hypothesis with 80% power. We performed immune correlative assays and sequencing of peripheral blood mononuclear cells (PBMCs) and primary amputation specimens.ResultsUnexpectedly, disease-free survival and overall survival were statistically inferior for dogs in the intent-to-treat population compared to a well-validated historical control cohort, so the trial was halted for futility. Cytotoxicity assays of PBMCs showed significant decreases after both surgery and chemotherapy with an overall decrease from the start to end of therapy (-18.2 ± 16.1%, P<0.001). Some dogs demonstrated positive fold change in PBMC cytotoxicity, which correlated significantly with improved dog survival (P = 0.004, r=0.62). Although plasma concentrations of key cytokines varied markedly with no significant differences between disease-free and metastatic-failure patients, inflammatory cytokines such as IL-6 showed absolute increases post-amputation and post-chemotherapy, correlating with decreases in cytotoxicity. Tumor sequencing data reproduced immune signatures as observed in both human and canine cohorts, and PBMC single cell sequencing data showed that gene expression profiles of NK and T cells were significantly different between short and long disease-free interval subjects.ConclusionsInhaled rhIL-15 combined with amputation and chemotherapy is associated with worse outcomes in dogs with OSA. Correlative assays suggest significant immunological effects of amputation and chemotherapy on immune responses. These data have important implications on novel immunotherapy strategies involving multimodality approaches including surgery and chemotherapy.